The strange case of the tetragenous Anodonta anatina. Issue 1 (3rd November 2015) - Lopes‐Lima, Manuel; Hinzmann, Mariana; Teixeira, Amílcar; Varandas, Simone; Machado, Jorge; Sousa, Ronaldo; Froufe, Elsa
ABSTRACT: Unionoid freshwater mussels have a unique life cycle with a form of parental care where the larvae are developed and kept inside the gills until release, followed by an obligate parasitic stage on fish. The size and location of the marsupium have been used as important phylogenetic characters in unionoids and in Anodontini its location was described exclusively on the outer demibranchs. Two recent surveys in a lake in the North of Portugal revealed large anodontine mussels morphological identical to Anodonta anatina but with glochidia in both demibranchs and with an unusual large size. In order to establish the identity of these mussels, a barcoding approach was used and an anatomical description of the gills and glochidia was performed. These mussels were identified as A. anatina and presented an inner demibranch pair with tripartite tubes. The glochidial sizes were much higher than previously reported for the species reaching maximum (length × height) values of 566 × 552 μm. This species reveals a high ecological plasticity being able to change its size and anatomy to increase its fertility as well as infestation performance. J. Exp. Zool. 325A:52–56, 2016 . © 2015 Wiley Periodicals, Inc.